The Impact of Mobile Augmented Reality on Vocabulary Acquisition, Learner Engagement, and Experience in Higher Education - DE VEGA, Nofvia; RAFIQA, Syarifa (Research and Innovation in Applied Linguistics, 2025)
The primary objectives of this study were to (1) assess the effectiveness of a Mobile Augmented Reality (AR)-based English learning program and (2) provide a human-centered analysis of students lived experiences within this innovative pedagogical setting. This work fills a critical research gap where much of the existing literature on AR in language learning emphasizes quantifiable results at the expense of students' subjective experiences and challenges. Utilizing a convergent parallel mixed-methods design, this study quantified English proficiency improvements and explored student experiences (interviews/observations). 173 diverse students engaged with a Mobile AR program featuring interactive 3D visualizations and customized content to enhance overall English, vocabulary, and grammar skills. The primary outcomes revealed a statistically significant and practically substantial positive impact of the AR intervention across all English language proficiency measures (p < 0.001; Cohen's d > 1.95; N-gain 0.74-0.75). Qualitative findings indicated that Mobile AR significantly enhanced comprehension through visualization, substantially increased learning interest and immersion, and fostered a deeper understanding of English's practical relevance through major-specific content. However, students reported challenges, notably technical issues such as device compatibility problems and occasional unstable internet connectivity. Future research should prioritize optimizing AR integration strategies and infrastructure development for wider, sustainable pedagogical application